Training loads and practices of competitive organ-recipients at the British and World Transplant Games - Hames, Thomas; Leddington-Wright, Sheila; Thake, C. Douglas; De Smet, Stefan; Price, Mike (Frontiers in Sports and Active Living, 2024)
Background: Little information is available regarding the TL and training practices of competitive athletes who are solid-organ recipients. This study characterized TL and practices of competitive organ-recipients at the British and World Transplant Games, 2017. Methods: Questionnaire data was gathered from 220 participants regarding sporting events and type, frequency, duration and intensity of training sessions undertaken. TL for each training session (session duration x session rating of perceived exertion [RPE]) and total TL were determined. Results: Overall participants trained 5 ±3 times per week at an RPE of 5 ±2 AU for between 60-75 min per session (TL ~1500 to 1875 AU). Most participants (n=176; 79.7%) reported training three or more times each week. Approximately half (49%) the participants reported undertaking resistance training each week (3 ±2 sessions per week, RPE of 6 ±2 AU, 45-60 minutes per session; TL ~810 to 1080 AU, respectively). Of those participants undertaking resistance training 75% undertook two or more sessions each week. Participants generally undertook most events within a predominant sport with one or two events in a secondary sport. Typical weekly TL for the whole group was 2762 ±3583 AU with considerable variation within and across sports (cycling 4383 ±4005 AU; field athletics 3671 ±6181 AU; court-based sports 2645 ±3308 AU; high physical demand sports [e.g. skiing, triathlon] 2595 +2247 AU; track athletics 2547 ±2664 AU; swimming 2091 ±1070 AU; low physical demand sports [e.g. darts, petanque, walking] 1182 +801 AU). Sports-specific TL for predominant and secondary sports was ~1500 AU. Resistance training and gym-based aerobic training were the most frequent non-specific training components undertaken. Most competitors (79%) were active in sport prior to transplant. Conclusion: The wide range of TL and components undertaken by athletes with solid-organ transplants likely reflects the multiple and diverse event participation of competitive organ-recipients as well as well as the diverse physical fitness profiles and incentives to participate. Optimization of TL both for multiple competitive sports and maintenance of health should be considered for these athletes.